2003
DOI: 10.1261/rna.2128903
|View full text |Cite
|
Sign up to set email alerts
|

An uncapped RNA suggests a model for Caenorhabditis elegans polycistronic pre-mRNA processing

Abstract: Polycistronic pre-mRNAs from Caenohabditis elegans operons are processed by internal cleavage and polyadenylation to create 3' ends of mature mRNAs. This is accompanied by trans-splicing with SL2 ∼100 nucleotides downstream of the 3' end formation sites to create the 5' ends of downstream mRNAs. SL2 trans-splicing depends on a U-rich element (Ur), located ∼70 nucleotides upstream of the trans-splice site in the intercistronic region (ICR), as well as a functional 3 end formation signal. Here we report the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…Overall, these results provide evidence that RNAPII is pausing at all 3 0 ends in operons, suggesting that internal 3 0 ends in operons is primed for termination but is prevented by a mechanism other than affecting RNAPII or CstF recruitment. Liu et al, 65 proposed that RNA-PII is prevented from terminating at internal 3 0 ends by a factor bound to the Ur element, a sequence between operon genes required for SL2 trans-splicing. This factor could temporarily block the passage of the XRN-2 exonuclease until SL2 trans-splicing provides a cap to the downstream RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results provide evidence that RNAPII is pausing at all 3 0 ends in operons, suggesting that internal 3 0 ends in operons is primed for termination but is prevented by a mechanism other than affecting RNAPII or CstF recruitment. Liu et al, 65 proposed that RNA-PII is prevented from terminating at internal 3 0 ends by a factor bound to the Ur element, a sequence between operon genes required for SL2 trans-splicing. This factor could temporarily block the passage of the XRN-2 exonuclease until SL2 trans-splicing provides a cap to the downstream RNA.…”
Section: Discussionmentioning
confidence: 99%
“…A likely possibility is that the SL2 trans-splicing that co-occurs with 3 0 end formation provides a 5 0 cap to the downstream RNA, so the XRN2 exonuclease cannot act to cause termination by the usual torpedo mechanism. 65 CstF50 plays a role in CstF64 localization upstream of the cleavage site…”
Section: Cstf Distribution On C Elegans Operonsmentioning
confidence: 99%
“…Sequences required for 39-end cleavage are also required for SL2 transsplicing. Following cleavage catalyzed by the cleavage and polyadenylation specificity factor (CPSF) bound at the AAUAAA just 59 of the cleavage site and cleavage stimulatory factor (CstF) bound to U-rich sequences in the vicinity of the cleavage site (Salisbury et al 2006), the 39 portion of the pre-mRNA is degraded exonucleolytically 59 to 39 until the nuclease reaches a block, possibly a bound protein (Liu et al 2003). CstF has been shown to interact with the SL2 snRNP, and mutations within the third stem-loop of SL2 RNA that eliminate this binding prevent its trans-splicing at operon trans-splice sites (Evans et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the stem or anything bound to it may block 59-to-39 exonucleolytic RNA degradation following cleavage at the 39 end of the upstream gene. Supporting this, the laboratory (Liu et al 2003) has reported previously the existence of a ''Ur RNA'' from the gpd-2/gpd-3 transgenic operon with a 59 end 4 nt upstream of the Ur element stem, a location dependent on the position of the Ur element.…”
Section: The Stem-loop Of the Ur Elementmentioning
confidence: 65%
“…Downstream operon genes are not cotranscriptionally capped; therefore, upstream gene 39 end cleavage would leave an unprotected 59 end on the downstream premRNA. The uncapped mRNA would likely be rapidly degraded 59 to 39 (Liu et al 2003). Linking the cleavage that generates the uncapped 59 RNA end with trans-splicing that provides a 59 TMG cap would ensure protection of the downstream mRNA, as well as prevent transcription termination that is associated with 39 end formation.…”
Section: Concurrent Transcription Is Not Required For Sl2 Specificitymentioning
confidence: 99%